Development of mobile application for soundscape evaluation - Ong, Zheng Ying (Nanyang Technological University, 2021)
The United Nations (UN) has laid out 17 sustainable development goals (SDGs) for all countries to achieve a more sustainable future by 2030. These goals provide an important framework for countries to recover from the COVID-19 pandemic. Although not explicitly stated in the SDG indicators, environmental noise has been labelled as an underestimated threat by the World Health Organisation (WHO) and is often referred to as the “new secondhand smoke”. The purpose of this project is to build a native mobile application that records both audio and visual input and relevant metadata for reporting soundscapes, together with a guided questionnaire to capture the users’ subjective assessment of the soundscape. The result of this project is to foster a participatory approach to urban noise monitoring and assessment by taking a gamified citizen science approach to soundscape assessment.